Extension actions to promote oral health for children in Specialized Early Childhood Education Institutions: experience report (Research, Society and Development, 2022)
This is a descriptive study of the experience report type, aiming at describing the oral health education actions developed by the project "Attention in Oral Health for School and Community" by the State University of Londrina at the SECE with children with disabilities aged 0 to 12 years. For that, the EA were previously scheduled with the SECE. Initially, the bond between child and student was strengthened at the place through interactions, Dental plaque disclosing agents and lectures on oral health. Subsequently, the student took each child to the toothbrush to teach and practice tooth brushing. For the babies, guidance was given on oral habits to the teachers and then the oral cavity was cleaned with gauze soaked in filtered water or Sodium Chloride. At the end, each participating child received a toothbrush and a fluoride toothpaste. These activities were carried out in 2021 and 2022, with the participation of 87 (eighty-seven) undergraduate students and 4 (four) professors of the Dentistry Course, 1 (one) oral health technician and 1 (one) driver. Extension actions are powerful instruments for the adherence and practice of positive habits to oral health, directly impacting the well-being and self-esteem of children. Them require leadership, empathy and social commitment from all the actors involved to achieve successful actions and student co-responsibility for training supported by the real problems encountered in society.